Tepung ubi kayu (manihot esculenta) dan tepung tempe kedelai mempengaruhi pengembangan volume dan mutu gizi protein roti tawar - Nanik Hamidah; Anang M Legowo; Syaiful Anwar (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Backround: Bread was a carbohydrate source’s food, was made from wheat flour.  Cassava flour as substitution for wheat flour by modification process used physic method (boiling) to obtain resitant starch. Collaboration cassava flourwith tempeh flour to add protein velue. The research for attest substitution wheat flour with cassava flour and tempeh flour influence to volume characteristics and quality of protein nutrient for white breadMethods:The research methods used exsperiment with completely randomized design which consists of 5 treatment with 4 replications. Cassava flour was processed by modification used physical methods (boiling).Proportion for tempeh and cassava flour 0%, 6%, 12%, 18%, 24% combinated by tempeh flour proportion 3:1. Dependent variabel were size of volume white bread, quality of protein nutrient.  Data Analysis used Anova. Result:The result of those research were found that the best chararacteristic from white bread was treatment 6%. Size of volume 3,15ml/g was size volume bread from composite flour ingredient. Quality of nutrient for protein consist of protein content increased from 6,15% to 8,76%, protein digestibility increased from 11,7% to 13,83%was compared for treatment 0%. Conclusion: Substitution wheat flour with cassava flour and tempeh flour influence white bread organoteptic (texture, colour (crumb, crust), taste), size of quality of nutrient protein.